2020
DOI: 10.13189/ujer.2020.082643
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Academic Integrity Breach among Malaysian University Students

Abstract: The objective of this article is to evaluate the knowledge and sources of knowledge of academic integrity and the types of academic integrity breach among university students in Malaysia. A quantitative approach was used to obtain the data. A set of questionnaires was distributed to students from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
0
4
0
2
Order By: Relevance
“…Para sukarelawan melibatkan diri dalam khidmat bantu meningkatkan kualiti kehidupan masyarakat seperti menyediakan pemeriksaan kesihatan dan vaksinasi percuma, menyediakan bantuan kebajikan, atau membantu melindungi alam sekitar (Normah & Ain Zahirah, 2021). Persediaan aspek penjagaan terhadap perlengkapan dan kesihatan fizikal sukarelawan penting bagi mengurangkan risiko kecederaan dan masalah kesihatan semasa sukarelawan terlibat dalam khidmat bantuan bencana (Nur Hafizah et al, 2020). Selain itu, kemahiran insaniah atau soft skills adalah kemahiran yang harus dimiliki oleh golongan sukarelawan melalui pengembangan kemahiran generik meliputi aspek kognitif, seperti nilai-nilai positif, kepemimpinan, kerjasama berpasukan, kemahiran berkomunikasi, dan proses pembelajaran yang berterusan (Intan et al, 2022).…”
Section: Konsep Kesukarelawanunclassified
See 1 more Smart Citation
“…Para sukarelawan melibatkan diri dalam khidmat bantu meningkatkan kualiti kehidupan masyarakat seperti menyediakan pemeriksaan kesihatan dan vaksinasi percuma, menyediakan bantuan kebajikan, atau membantu melindungi alam sekitar (Normah & Ain Zahirah, 2021). Persediaan aspek penjagaan terhadap perlengkapan dan kesihatan fizikal sukarelawan penting bagi mengurangkan risiko kecederaan dan masalah kesihatan semasa sukarelawan terlibat dalam khidmat bantuan bencana (Nur Hafizah et al, 2020). Selain itu, kemahiran insaniah atau soft skills adalah kemahiran yang harus dimiliki oleh golongan sukarelawan melalui pengembangan kemahiran generik meliputi aspek kognitif, seperti nilai-nilai positif, kepemimpinan, kerjasama berpasukan, kemahiran berkomunikasi, dan proses pembelajaran yang berterusan (Intan et al, 2022).…”
Section: Konsep Kesukarelawanunclassified
“…Golongan sukarelawan berhadapan dengan cabaran keselamatan diri. Memberi keutamaan terhadap aspek keselamatan dan kesihatan diri merupakan salah satu tanggungjawab yang perlu diberi perhatian (Nur Hafizah et al, 2020). Informan 1 menjelaskan: "Risau kadang-kadang dengan keselamatan diri mereka.…”
Section: Keselamatan Diri Sukarelawanunclassified
“…Another study by Bloomfield et al (2021) found that 69% of health students in Southeast Asian countries have ever been involved in academic cheating. The subsequent studies by Kassim et al ( 2019) and Yusoff et al (2020) found that many students in Malaysia are involved in academic cheating, as well as in Pakistan, Thailand and Indonesia (Iqbal et al , 2021; Septiana and Bachtiar, 2020; Thomas, 2017). The results of these figures provide evidence that academic cheating has not only spread to Europe, but also to the Asian region.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we expand the context to three countries in Asia (Indonesia, Malaysia and Thailand). There are several common characteristics among these three countries: first, they are members of the same Association of Southeast Asian Nations family and have a similar collectivist culture (Pariyanti et al , 2022b; Pinasti and Adawiyah, 2016; Thomas, 2017; Yusoff et al , 2020). More broadly, Dendir and Maxwell (2020) found social and cultural norms to play a role in academic dishonesty in higher education.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation